2021
DOI: 10.1080/09669760.2021.1983775
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ beliefs about peer social interactions and their relationship to practice in Chinese inclusive preschools

Abstract: As previous research indicated that children with special educational needs are at risk of social exclusion, this study investigated the link between teachers' beliefs about children's social peer interactions and their teaching practices. Using a qualitative case study examining seven teachers from four inclusive classes at one preschool in Shanghai, data from interviews and participatory observations were triangulated. Three degrees of (in)consistencies when combining interviews (teachers' beliefs) and obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Parents should be aware of guiding their ASD children to make friends with peers without ASD in daily life. They are also expected to collaborate with kindergarten teachers and actively participate in kindergarten activities (Tan et al, 2022). Future studies could further explore effective methods for teachers and parents to promote ASD children's positive peer relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Parents should be aware of guiding their ASD children to make friends with peers without ASD in daily life. They are also expected to collaborate with kindergarten teachers and actively participate in kindergarten activities (Tan et al, 2022). Future studies could further explore effective methods for teachers and parents to promote ASD children's positive peer relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified that the erroneous conceptions of teachers toward students with ASD are linked to the lack of knowledge on how to communicate with them and understand their behaviour [77][78][79]. The inclusion of students with social difficulties and behavioural problems generates great challenges [22,23], and the support among teachers in designing classes or materials, mutual observation, co-teaching, sharing experiences, etc. is identified as a fundamental strategy to develop inclusive contexts [73,80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this work is also focused on the analysis of this central dimension of inclusion in a group of students in situations of special vulnerability to exclusion processes, such as those with special educational needs (SEN) and, more specifically, in those specially challenging to teachers: students with ASD [20,21]. In this line, previous studies show that the inclusion of both students with social difficulties and those with behavioural problems generates more challenges than the inclusion of students with other types of SEN [22,23]. Precisely the importance of this dimension in these students has been highlighted by teachers, families, and students themselves, although research has focused more on stages after Early Childhood [24].…”
Section: Introductionmentioning
confidence: 99%
“…Es necesario señalar que, estos programas de co-docencia deberán tener como objetivo la plasmación de una educación diferenciada y personalizada en los distintos entornos educativos; como, por ejemplo, el vertimiento de clases regulares, aunque inclusivas, que mejoren la experiencia en inclusión de los estudiantes con NEE en la escuela, de tal manera, que los alumnos con y sin NEE compartan experiencias de aprendizaje (Lindner et ál., 2021;Tan, 2022;Alnahdi et ál., 2022).…”
Section: Desarrollo Y Discusiónunclassified